Bovine hydroxyapatite (BHA) Boron Oxide Composites - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2009)
Composites of calcinated bovine bone derived hydroxyapatite (HA) with 5, 7.5 and 10 wt % B2O3 were prepared by sintering. The production of HA from natural sources is preferred due to economical and time saving reasons. In this study scanning electron microscopy (SEM) investigations, microhardness and compression strength measurements were performed on composites. The experimental results indicated that compression strength and microhardness of HA-boron-oxide composites decrease when the content of boric acid and sintering temperature increase. The best mechanical properties achieved for 5 wt % addition of dehydrated boric acid. It was seen that at higher sintering temperatures, the compression strength and the microhardness decrease due to the very intensive pore formation. The results agree fairly well with microstructure analysis.
Keywords: Hydroxyapatite; Boric Acid; Sintering; Microstructure; Mechanical Properties; MECHANICAL-PROPERTIES; CERAMICS